2016
DOI: 10.1248/bpb.b15-00835
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Characterization of Derrone as an Aurora Kinase Inhibitor

Abstract: Among mitotic kinases, Aurora kinases are the most widely studied, since their expression is restricted to mitosis. They play a key role in chromosome segregation and cell polyploidy. Aurora kinases are important therapeutic targets, and several research groups have directed their efforts toward the identification of kinase inhibitors. The aim of this study is to screen and characterize Aurora kinase inhibitors from natural substances extracted from plants that are used in the Vietnamese pharmacopoeia. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…For example, AKI-001 [100], BPR1K871 [89], CCT137690 [97,98], JNJ-7706621 [92], SAR156497 [93], SCH-1473759 [90] and VE-465 [95] have potent inhibitory effects on Aurora kinase activity with IC50 values< 50 nM. Other Aurora kinase inhibitors with IC50 values> 50 nM against kinase activity, such as BPR1K653 [87], CCT129202 [96], derrone [91], PHA-680632 [99], R1498 [94], reversine [101] and TY-011 [88], have also been tested in preclinical studies, and the preliminary data are shown in Table 3. U14 cell xenograft; mice were treated with reversine (10 mg/kg) alone or with aspirin (1 μg/kg), i.p per 3 days; tumor growth was reduced and the mice survived longer in the combination group.…”
Section: Pan Aurora Kinase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, AKI-001 [100], BPR1K871 [89], CCT137690 [97,98], JNJ-7706621 [92], SAR156497 [93], SCH-1473759 [90] and VE-465 [95] have potent inhibitory effects on Aurora kinase activity with IC50 values< 50 nM. Other Aurora kinase inhibitors with IC50 values> 50 nM against kinase activity, such as BPR1K653 [87], CCT129202 [96], derrone [91], PHA-680632 [99], R1498 [94], reversine [101] and TY-011 [88], have also been tested in preclinical studies, and the preliminary data are shown in Table 3. U14 cell xenograft; mice were treated with reversine (10 mg/kg) alone or with aspirin (1 μg/kg), i.p per 3 days; tumor growth was reduced and the mice survived longer in the combination group.…”
Section: Pan Aurora Kinase Inhibitorsmentioning
confidence: 99%
“…Researchers can take advantage of the high-resolution 3D protein structures and computer docking tools to find natural compound or FDA approved drugs that target AURKA. For example, derrone, extracted from erythrina orientalis, is screened from 100 natural substances to inhibit AURKA kinase activity and cell growth [91]. Another case is bioactive tanshinone I which is from traditional Chinese herbal medicine Salvia miltiorrhiza.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…The tumor growth of MCF‐7 spheroids decreased in the presence of derrone. After 15 days of treatment, tumor spheroid growth inhibition (%TGI) was 17.5% and 65.4% for 30 and 60 µM, respectively (Hoang et al., 2016).…”
Section: Akis Of Natural Originmentioning
confidence: 99%
“…Some closed effects can also be observed with respect to AIF in lung cancer and leukemia cells (see above). Nonetheless, its cellular effects are also ascribed to its strong inhibitory effects against Aurora kinases A and B, with the respective IC 50 of 22.3 µM and 6 µM in direct kinase inhibition assays [ 50 ]. Aurora kinases are essential serine/threonine kinase proteins, used during mitosis via their key roles in chromosomal segregation and cell polyploidy [ 50 ].…”
Section: In Vitro Anticancerous Activities Of Compounds From E Senegalensis : Mechanisms Of Actionmentioning
confidence: 99%
“…Nonetheless, its cellular effects are also ascribed to its strong inhibitory effects against Aurora kinases A and B, with the respective IC 50 of 22.3 µM and 6 µM in direct kinase inhibition assays [ 50 ]. Aurora kinases are essential serine/threonine kinase proteins, used during mitosis via their key roles in chromosomal segregation and cell polyploidy [ 50 ]. Their overexpression in many cancers including colon, breast, prostate, pancreatic and thyroid cancer is associated with advanced stages and poor prognosis [ 77 ].…”
Section: In Vitro Anticancerous Activities Of Compounds From E Senegalensis : Mechanisms Of Actionmentioning
confidence: 99%